Color texture feature selection by MIFS for image classification - Maia, H. E.; Hammouch, A.; Bakrim, M. (2010)
The work presented in this article consists in evaluating the contribution of the use of a texture-color combination in forest mapping. We transform a Spot image into different color spaces, then we extract nine parameters using Laws filter. The resulting set of parameters is reduced using MIFS algorithm based on mutual information. The results are promising and give satisfying classification results.
The following values have no corresponding Zotero field: secondary-title: I/V Communications and Mobile Network (ISVC), 2010 5th International Symposium on periodical: I/V Communications and Mobile Network (ISVC), 2010 5th International Symposium on pages: 1-4 isbn: VO - electronic-resource-num: 10.1109/ISVC.2010.5656251
Keywords: Classification; Color; Laws filter; MIFS; Texture